One of the important factors for the management activity at Salak Mountain is the presence of Salak Mountain’s vegetation classification, which until recently has never been done. The research objectives were to classify the variety of vegetation types at Salak Mountain. Vegetation sampling was made with systematic sampling with random start. Vegetation type at alliance level was determined with vegetation ordination. Three vegetation alliances can be extracted from the ordination. These allianc - Muhammad Wiharto; Cecep Kusmana; Lilik Budi Prasetyo; Tukirin Partomihardjo (Forum Pasca Sarjana, 2008)
One of the important factors for the management activity at Salak Mountain is the presence of Salak Mountain’s vegetation classification, which until recently has never been done. The research objectives were to classify the variety of vegetation types at Salak Mountain. Vegetation sampling was made with systematic sampling with random start. Vegetation type at alliance level was determined with vegetation ordination. Three vegetation alliances can be extracted from the ordination. These alliances are Shcima walichii-Pandanus punctatus/ Cincora sinensis forest alliance; Glocidion apus-Mallotus blumeana/Chima sinensis forest alliance; and Pinus merkusii-Dysoxiylum arborescens/Dysoxiylum dichotoma forest alliance. Vegetation alliances are forming mainly because of their similarity in their structure, composition, and physiognomy of vegetation. The abiotic factors that consistently differentiate alliance 1 with the other alliances are N total, dust content of the soil, and slope. P soil’s content is the abiotic factor that consistently differentiates alliance 2 with the other alliances, while C organic soil’s content and cation exchange capacity of the soil are the abiotic factors that consistently differentiate alliance 3 with the other alliances. There are five vegetation association at allinace 1, six alliance 2 and seven at alliance 3. Each dominant spesies has uniquely preference to abiotic factor in their distribution at Gunung Salak. Stand structures of alliance 1 and 3 forming J reverse curve. Key words: association, ordination, Salak Mountain, vegetation alliance, vegetation classification